Formulation and Evaluation of Elephant Ginger Essential Oil-Chitosan Nanospray: Antibacterial Activity against P. gingivalis ATCC 33277 and Cytotoxicity on Gingival Fibroblasts - Indira Larasati Dewi; Archadian Nuryanti; Indah Titien Soeprihati; Sri Raharjo; Qurrotul A'yun (Cakradonya Dental Journal, 2026)
In the oral cavity, Porphyromonas gingivalis is a dominant periodontal pathogen associated with gingivitis. Elephant ginger essential oil exhibits antibacterial properties, while chitosan functions as a drug delivery agent that enhances the bioavailability of active compounds. This study aimed to evaluate the effectiveness of nanosprays combining elephant ginger essential oil and chitosan in inhibiting P. gingivalis ATCC 33277 growth and to assess the effect of increasing essential oil concentration on human gingival fibroblast (HGF) cell viability. This in vitro experimental study included nanospray formulations containing ginger essential oil at concentrations of 7.5%, 12.5%, and 17.5% combined with 1% chitosan. Antibacterial activity was assessed using the agar diffusion on Mueller–Hinton agar with five replicates. HGF cell viability was evaluated using the MTT assay at 24, 48, and 72 hours. Data were analyzed using one-way ANOVA, post-hoc LSD tests, Spearman correlation, and linear regression. All nanospray formulations met the standards for nanoemulsion and oral spray preparations. The largest inhibition zone was observed in the 17.5% group (17.87 mm). All nanosprays significantly inhibited P. gingivalis (p= 0.000); however, increasing essential oil concentration reduced HGF cell viability. The nanospray containing 12.5% elephant ginger essential oil and 1% chitosan is the optimal concentration, maintaining the ISO-recommended safety limit of 70% cell viability while providing effective antibacterial activity for the management of gingivitis, particularly in pediatric patients.